Inter-firm linkages, business strategies and firm performance: an empirical study of small industrial clusters in Central Java, Indonesia - Heotoro, Arif; Abdullah, Moha Asri (IIUM Press, 2015)
Inter-firm linkages and business strategies serve as an important instrument for the way of small industrial cluster development in developing countries. The present study utilizes the case of selected manufacturing micro and small enterprises (MSEs) that operate in various small industrial clusters in Central Java, Indonesia. The focus of this study is to examine the relationships between inter-firm linkages and business strategies applied simultaneously by MSEs and their impacts on firm performance. From the perspective of co-opetition strategy, the results of this study revealed that some types of inter-firm linkages and business strategies matter for firm performance. However, inter-firm linkages seem to be less effective compared to business strategies in affecting firm performance in this study.